Optimising Green Industry Development to Strengthen the National Economy (Jurnal Lemhannas RI, 2024)
Purpose: The study analyses the current status of green industry development in Indonesia, investigates the factors influencing its progress, and proposes optimisation strategies to support a sustainable national economy.Study Design/Methodology/Approach: A descriptive research method is applied using the PESTLE (Political, Economic, Social, Technological, Legal, and Environmental) framework. Data sources include comprehensive literature reviews, national policy documents, and industry performance reports.Findings: The study reveals that green industry development in Indonesia faces substantial obstacles, such as regulatory inconsistencies, limited access to local technological innovation, inadequate fiscal incentives, and a shortage of skilled human resources in green sectors. Despite these challenges, there are significant opportunities for improvement through enhanced technological innovation, strengthened cross-sector collaboration, expanded government incentives, and increased investment in green industries.Originality/Value: The study provides a novel contribution by presenting actionable strategies for optimising green industry development through regulatory harmonisation and multi-stakeholder collaboration. The insights offer policy recommendations designed to foster sustainable, inclusive, and competitive economic growth in alignment with national and international sustainability commitments.
Keywords: Green Industry; national resilience; optimisation; PESTLE; Sustainable economy